(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
An ESP32-based CNC Braille printer is a tactile printing device designed to emboss Braille dots using CNC motion control. It converts digital text into raised patterns readable by touch, aiding visually impaired users. Compared to Arduino, ESP32 offers superior processing speed and dual-core performance. Built-in Wi-Fi and Bluetooth enable wireless control and remote updates. The printer uses stepper motors and servo mechanisms for precise dot placement. ESP32 supports SPIFFS for onboard Braille file storage and retrieval. Voice input integration allows hands-free operation and accessibility. Real-time text-to-Braille conversion is faster due to ESP32’s higher clock rate. Arduino-based systems often require external modules for connectivity. ESP32’s larger memory supports complex firmware and multitasking. The printer can be controlled via mobile apps or web interfaces. It’s cost-effective and scalable for educational and assistive tech use. Open-source libraries and community support enhance development. The design promotes inclusive technology and digital literacy It bridges the gap between IoT and accessibility solutions. ESP32 makes Braille printing smarter, faster, and more connected.